Prevalence and Clinical Characteristics of Myelinated Retinal Nerve Fibres in a Chinese Teleophthalmology System. (2nd September 2021) - Li, Meng; Zhang, Xi-Fang; Yusufu, Mayinuer; Liu, Li-Juan; Wang, Shuang; Wang, Jin-Da; Zhang, Jing-Shang; Wang, Kai-Jie; Mao, Ying-Yan; Cao, Kai; Chen, Shu-Ying; Yao, Qin-Nan; et al.
ABSTRACT: Purpose : To investigate the prevalence and clinical characteristics of myelinated retinal nerve fibre (MRNF) in a large teleophthalmology system. Methods : All records between January 2015 and December 2015 from Daheng Prust teleophthalmology system were reviewed by 2 ophthalmologists independently. MRNF was classified into continuous group and discontinuous group according to the relationship between MRNF patches and optic disc. The number, total area and location of MRNF patches were analysed. Concomitant ocular diseases were documented. Results : Out of 51469 subjects, MRNF was detected in 304 eyes of 263 subjects with a prevalence rate of 0.51 ± 7.1% per subject and 0.30 ± 5.4% per eye. Among 304 eyes with MRNF, 239 (78.6%) eyes were in continuous group and 65 (21.4%) eyes were in discontinuous group. Single MRNF patch was found in 249 (81.9%) eyes and multiple MRNF patches were found in 55 (18.1%) eyes. MRNF of small size was found in 150 (49.3%) eyes. The ratios of multiple MRNF patches and small-sized MRNF in the continuous group were significantly higher than those in the discontinuous group ( P = .014 and P < .001). In continuous group, the MRNF patches were located most frequently in the superior region (68.6%) of the optic disc; In discontinuous group, the MRNF patches were located most frequently in the inferotemporal region (38.5%) of the retina. Epiretinal membrane (12 eyes, 3.9%) was the most common concomitant ocular disease. Conclusion : MRNF is uncommon in China. MRNF usually presents unilaterally and as a single small whitish patch that is connected with optic disc.